Feasibility of an EUS e-training course with live cases - Dhir, Vinay; Udawat, Priyanka; Shah, Rahul; Alahari, Aruna (Endoscopy International Open, 2021)
Background and study aims One-on-one endoscopic ultrasound (EUS) mentorship was not possible at most institutions during the COVID-19 pandemic. We decided to test the feasibility of structured training in EUS with virtual e-classes with live cases. The aim of this study was to assess the feasibility of a virtual EUS training course with objective end points.Patients and methods Twenty-one trainees were trained on a virtual platform over 16 classes of 90 minutes each, over 3 months. The virtual training screen had two equal parts, one showing the endoscopist’s hand movements, and another the resultant EUS display. The course curriculum included EUS anatomy of the mediastinum, pancreatico-biliary region and rectum. The assessment was done on videos of procedures performed by trainees.Results Twenty trainees performed 251 EUS procedures (range 8–25, mean 12.5 ± 4.9) at their institutions. At the end of the course, all students (100 %) could maneuver the echo-endoscope through to the duodenum. Fifteen trainees sent a video for final assessment. The successful specified area identification rates were 12 of 15 (80 %) for the subcarinal space, 10 of15 (66.6 %) for the head of the pancreas, 10 of 15 (66.6 %) for the common bile duct, and nine of 15 (60 %) for the tail of pancreas. The success rate of ability to get appropriate windows was 10 of 15 (67 %) for the subcarinal space, eight of 15 (53.3 %) for the head of the pancreas, seven of 15 (46.6 %) for the common bile duct and six of 15 (40 %) for the tail of pancreas. No adverse events were reported.Conclusions A virtual EUS training course with live cases appears feasible. It allows the possibility of training a large number of students. Further evaluation is needed, especially of virtual assessment methods and training benchmarks.